The Urgency of Dinar and Dirham as a Usury-Free and Maysir-Free Currency Solution - Yunus, Muhammad; Janwari, Yadi; Al-Hakim, Sofian (AL-ARBAH: Journal of Islamic Finance and Banking, 2024)
Money has an important role in human life, especially in economic activities. The history of money starts from the barter system to the use of gold and silver as a medium of exchange. In the Islamic perspective, money is seen as a medium of exchange and a measure of value, not as a commodity. Islam prohibits practices such as usury, gambling, and speculation that can cause injustice in the distribution of wealth. Islamic principles in terms of money include accountability, justice, simplicity, and the prohibition of the accumulation of wealth. Some people view the Dinar and Dirham currencies are Islamic currencies, so they forbid paper currency or fiat money from being used because the nominal value does not match the intrinsic value, unlike Dinar and Dirham currencies. The method of this research is qualitative research in the form of library research. The result of the discussion of this article is that the dinar and dirham currencies did not originate from Islam but from the Romans and Persians. There are 3 functions of money in Islam, namely: money as a means of unit price, money as a medium of exchange, and Money as a storage medium of value. Thus, the Islamic perspective on money aims to create a fair economic and financial system for all mankind. Keywords: Money; Dinar; Dirham